Estimation of Fluoride concentration in drinking water of Kathmandu Valley - Shah, Priyanka; Khanal, S (Nepal Medical College Journal, 2020)
Fluoride has a preventive effect on dental caries. However, excessive/insufficient ingestion of fluoride can lead to the development of dental fluorosis/increased risk for dental caries respectively. The objective of this study was to estimate fluoride concentration in drinking water of Kathmandu valley. It was a community based cross-sectional study in which drinking water samples were collected from municipal water supply and bottled water. Municipal water supply was collected according to eight water schemes in Kathmandu valley and as for bottled water, 35 samples were randomly collected according to different brand names available in the commercial market. The samples were analyzed for fluoride content by SPADNS colorimetric method as per standard procedure set by American Public Health Association (APHA 2012).The results revealed that the fluoride content in drinking water samples was below the permissible limit (<0.5 ppm) as per Nepal’s drinking water quality standards and WHO guidelines. Hence, implementation of water fluoridation program can be initiated for municipal water supply and bottled water for prevention of dental caries to optimize the oral health of people.